A controllable flower-like FeMoO4/FeS2/Mo2S3 composite as efficient sulfur host for lithium-sulfur batteries. (1st September 2020) - Chen, Zihe; Liao, Ao; Guo, Zhenzhen; Yu, Fang; Mei, Tao; Zhang, Zexian; Irshad, Muhammad Sultan; Liu, Chengcheng; Yu, Li; Wang, Xianbao
Abstract: As one of the most anticipated energy storage systems, the application of lithium-sulfur batteries is hindered by low conductivity of insoluble sulfur species (S8, Li2 S2 and Li2 S), the shuttle effect of soluble lithium polysulfides (Li2 Sx, 4 = x ≤ 8) and the volume expansion of sulfur species during the cycling. To overcome these barriers, a tunable geometry of flower-like FeMoO4 /FeS2 /Mo2 S3 composite is successfully investigated using simple one-step solvothermal technique. Fe-based sulfides with good conductivity and Mo-based sulfides with the efficient ability of catalytic sulfur species conversion are promising sulfur host for high performance lithium-sulfur batteries (LSBs). It should be noted that this is first time to introduce FeMoO4 as polysulfides anchoring material into the lithium-sulfur system. Consequently, the flower-like composite with 79 wt % sulfur loading exhibits a high initial capacity of 1600 mA h g −1 and a reversible capacity of 781 mAh g −1 after 300 cycles at 1 C. Even at a high rate of 10 C, a capacity of 421 mAh g −1 is maintained after 300 cycles. Graphical abstract: Image 1 Highlights: Flower-like FeMoO4 /FeS2 /Mo2 S3 composite is designed via one-step solvothermal means. Structure such as loose, closed, and open flower-like sphere can be designed. FeMoO4 with high adsorption energy is firstly introduced into LSBs. This composite exhibits a capacity of 611 mAh g −1 after 300 cycles at 5 C. For high rate performance, 421 mAh g −1 is achieved after 300 cycles at 10 C.